2016
DOI: 10.1097/hp.0000000000000444
|View full text |Cite
|
Sign up to set email alerts
|

Deposition Measurements From the Full-Scale Radiological Dispersal Device Field Trials

Abstract: In 2012, Defence Research and Development Canada led a series of experiments, titled the Full-Scale Radiological Dispersal Device Field Trials, in which short-lived radioactive material was explosively dispersed and the resulting plume and deposition were characterized through a variety of methods. Presented here are the results of a number of measurements that were taken to characterize the radioactive ground deposition. These included in situ gamma measurements, deposition filter samples, and witness plate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Doses decreased much more quickly in the crosswind directions. Erhardt et al (2016) reported that, of the approximately 35 GBq 140 La sources that were dispersed into the air during the three tests, between 15% and 30% of the material was deposited in the field within 450 m of ground zero. The ground shine dose rate profiles from the RadEye detector array measurements from this deposited material is shown for each shot in Fig.…”
Section: Equipment and Methodsmentioning
confidence: 97%
“…Doses decreased much more quickly in the crosswind directions. Erhardt et al (2016) reported that, of the approximately 35 GBq 140 La sources that were dispersed into the air during the three tests, between 15% and 30% of the material was deposited in the field within 450 m of ground zero. The ground shine dose rate profiles from the RadEye detector array measurements from this deposited material is shown for each shot in Fig.…”
Section: Equipment and Methodsmentioning
confidence: 97%
“…Measurements of the subsequent dispersion and deposition were made using multiple experimental techniques, details of which can be found in the overview papers in this special issue of Health Physics (Green et al 2016;Erhardt et al 2016). The data used in this model comparison study are briefly described here.…”
Section: Experimental Test Seriesmentioning
confidence: 99%
“…Measurements of the deposition are presented in three papers. Erhardt et al (2016) present deposition measurements taken using handheld and fixed-point, in situ, beta and gamma detectors, Sinclair et al (2016) present aerial survey measurements of the deposition, and Berg et al (2016) present laboratory analysis of measurements using passive deposition filters. Comparison of dispersion model results to the FSRDD Field Trial measurements and analysis of model performance are presented in four papers.…”
Section: Full-scale Radiological Dispersal Device Field Trialsmentioning
confidence: 99%